Local knowledge regarding trade-offs among coffee productivity and other ecosystem services in a range of different agroforestry systems in Central America - Cerdán Cabrera, Carlos Roberto (2012)
Tesis (Ph. D.) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), Bangor University, 2012